2020
DOI: 10.1002/ep.13570
|View full text |Cite
|
Sign up to set email alerts
|

Iron modified zeolite carrier for efficiently pharmaceutical pollutant degradation in heterogeneous electro‐Fenton: Influence factors and kinetic

Abstract: In this study, the high silica ZSM‐5 carrier was modified with the iron species and applied as a heterogeneous electro‐Fenton (EF) catalyst for pharmaceutical pollutant degradation. The carrier was prepared by the hydrothermal method and followed by impregnation. The physicochemical properties were evaluated by field emission scanning electron microscopes (FE‐SEM), FT‐IR, X‐Ray diffraction (XRD), and N2 adsorption–desorption techniques. The impregnated carrier had high crystallinity, high specific surface area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…60 Interesting results of the EF process have also been discussed. 53 It was found that the reaction was of pseudo-firstorder, and there was a removal of 92.5% at pH 3, 25 °C, current density 100 mA/cm 2 , and 0.2 g/L catalyst. The catalyst was recyclable and reusable due to its stability, and only a 0.5% loss of efficiency was found to reduce after each cycle.…”
Section: Advanced Filtration Methods (Afm)mentioning
confidence: 93%
See 1 more Smart Citation
“…60 Interesting results of the EF process have also been discussed. 53 It was found that the reaction was of pseudo-firstorder, and there was a removal of 92.5% at pH 3, 25 °C, current density 100 mA/cm 2 , and 0.2 g/L catalyst. The catalyst was recyclable and reusable due to its stability, and only a 0.5% loss of efficiency was found to reduce after each cycle.…”
Section: Advanced Filtration Methods (Afm)mentioning
confidence: 93%
“…Interesting results of the EF process have also been discussed . It was found that the reaction was of pseudo-first-order, and there was a removal of 92.5% at pH 3, 25 °C, current density 100 mA/cm 2 , and 0.2 g/L catalyst.…”
Section: Technologies Involved In Treatment Of Pharmaceutical Wastewatermentioning
confidence: 99%
“…The precipitation of Fe 3+ ions increase with increase in pH, which decreases the generation of Fe 2+ and subsequently decreases the process efficiency. The scavenging reaction of OH • by proton can reduce the oxidation ability of OH • (Adel Niaei & Rostamizadeh, 2021 ; Benzaquén et al, 2020 ). It should be noted that at higher pH values the production of OH • is lower, while proton salvation generates the hydroperoxonium ion from H 2 O 2 (El-Ghenymy et al, 2012 ).…”
Section: Influential Parameters On Heterogeneous Electro-fentonmentioning
confidence: 99%